Role of AccMGST1 in oxidative stress resistance in Apis cerana cerana - Zhao, Wenchun (Cell Stress Chaperones, 2019)
As detoxification enzymes, proteins in the glutathione S-transferase (GST) superfamily are reported to participate in oxidative stress resistance. Nevertheless, microsomal GSTs (MGSTs), a unique subclass of the GST superfamily associated with membranes, are rarely studied in insects. Here, we isolated an MGST gene in Apis cerana cerana (AccMGST1) and verified its role in oxidative stress response. We found higher expression of AccMGST1 in protective or defensive tissue, that is, the epidermis, which indicated its role in stress resistance. Real-time quantitative PCR (qRT-PCR) analysis indicated that AccMGST1 was upregulated by oxidative stresses at the transcriptional level. In contrast, AccMGST1 expression was inhibited when the antioxidant vitamin C (VC) was fed to experimental bees. Through western blotting, we found that the protein level of AccMGST1 under oxidative stress corresponded to the transcript level. Disc diffusion and mixed-function oxidation (MFO) assays suggested that AccMGST1 can protect not only cells but also DNA against oxidative damage. Furthermore, we discovered that the expression patterns of known antioxidant genes were changed in A. cerana cerana after AccMGST1 was silenced by RNA interference (RNAi). Thus, we concluded that the gene AccMGST1 exerts a significant role in the antioxidant mechanism. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12192-019-01007-w) contains supplementary material, which is available to authorized users.